KOMUNITAS MUDA MODERN: ANTARA TRADISI DAN IDENTITAS RELIGIUS DI DESA DOLOK MASANGO, KECAMATAN BINTANG BAYU, KABUPATEN SERDANG BEDAGAI - Ayunda, Zalika; Harahap, Indra (Yayasan Amanah Nur Aman, 2025)
In the digital age, marked by advances in information technology and the expansion of social media, the religious identity of young people has undergone significant transformation. This study examines how the younger generation, particularly Indonesian Muslim youth, form and express their religious identity through digital spaces. Using a qualitative approach based on recent studies (2019–2025), it was found that digital media serves a dual role as both a platform for spiritual learning and a space for negotiating values. Adolescents are no longer passive recipients of religious teachings but active agents in constructing religious narratives that align with their context. The concepts of hybrid identity, online hijrah communities, and communicative religious practices have become new patterns in the religiosity of Generation Z. However, these dynamics also present challenges such as value fragmentation and superficial religious symbolism. This study recommends a more reflective, participatory, and adaptive approach to religious education that is responsive to digital culture as a strategy to strengthen the spirituality of teenagers in a holistic manner.